High‐throughput screening of measuring conditions for an optimized SERS detection1. (22nd December 2015) - Kämmer, Evelyn; Olschewski, Konstanze; Rösch, Petra; Weber, Karina; Cialla‐May, Dana; Popp, Jürgen
Abstract : Surface‐enhanced Raman spectroscopy (SERS) is a perfect method for analytical applications because of delivering specific molecular information combined with a high sensitivity when applying rational design metallic nanostructures. However, the pH level and the activation of ctheir mutual influence. Besidesolloidal SERS substrates influence the sensitivity and comparability of the SERS analysis. In this study, a routine is presented that allows for a fast and effective recognition of the influences of pH and activating agents on the SERS signal of an analyte molecule. To do so, a citrate‐reduced Ag colloid served as SERS substrate. The influence of four activating agents as well as five pH levels on the SERS signal of the model analyte melamine was investigated. Here, not only the influence of the anion but also that of the cation of the activating agents was examined. In addition to different signal intensities, a shift of the dominant melamine signal occurred depending on the adjusted conditions. At pH 11, the lowest intensities of the SERS signal from the model analyte melamine were detected. The maximal enhancement of the ring breathing II mode in combination with this specific colloid was achieved using sodium chloride as an activating agent at a pH level of 5. Thus, the study introduces a routine, which can be applied on various analyte molecules to optimize the SERS intensity by changing the activation agent as well as the pH. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The influence of different pH and activating agents on the SERS signal of the model analyte melamine was investigated. The usage of a lab‐on‐a‐chip device enables the design of gradients, which in turn allows a standardization and comparability of the different experiments.